1981
DOI: 10.1073/pnas.78.10.6509
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostate tumor growth in two rat models by chronic administration of D-Trp6 analogue of luteinizing hormone-releasing hormone.

Abstract: days decreased the weights of both the ventral prostate and testes but had no effect on the weight ofthe anterior pituitary gland. The percentage increase in tumor volume was decreased to one-third and the actual tumor weight was decreased by 58% compared to untreated controls. The tumor doubling time was more than 4 times longer in rats receiving D-Trp6-LH-RH than in controls. Serum levels of luteinizing hormone and follicle-stimulating hormone were significantly decreased in rats receiving this analogue. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 21 publications
2
78
0
1
Order By: Relevance
“…This is probably because deslorelin is not cytotoxic to the cells. However, LHRH superagonists such as deslorelin might inhibit tumor growth after prolonged treatment by suppressing production of testosterone, which is implicated in tumor growth (44). Other studies have shown that LHRH analogues act on tumor cells by interfering with the tyrosine kinase activity (45).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because deslorelin is not cytotoxic to the cells. However, LHRH superagonists such as deslorelin might inhibit tumor growth after prolonged treatment by suppressing production of testosterone, which is implicated in tumor growth (44). Other studies have shown that LHRH analogues act on tumor cells by interfering with the tyrosine kinase activity (45).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the existence of this receptor was demonstrated in mouse and rat nude models (103,104), as well as in human prostate cancer biopsy (99). Based on the above evidence, several research groups have been employing GnRH analogs as antineoplastic drugs (102,(105)(106)(107)(108)(109). GnRHR and GnRH in prostate cancer are able to promote a high diminution in cellular proliferation (100,101).…”
Section: Gnrhr and Ovarian Cancermentioning
confidence: 96%
“…[1][2][3][4][5][6][7] GnRH agonists induce cell cycle arrest in the Go/G1 phase, but the detailed molecular mechanism is unknown. One of the proposed mechanisms of the antitumor effect of GnRH agonists is the downregulation of GnRH receptor (GnRH-R) activity in the pituitary gland that results in inhibition of sex steroid secretion in patients with premenopausal breast cancer or prostate cancer.…”
Section: Introductionmentioning
confidence: 99%